CUSTOMS WHICH ARE CARRIED OUT BEFORE THE WEDDING, ON THE DAY OF THE WEDDING AND AFTER THE WEDDING IN UZBEK AND GERMAN PEOPLE (Scientific journal of the Fergana State University, 2024)
In this article, wedding ceremonies in Uzbek and German languages and features of small ceremonies held before, on the wedding day and after the wedding, similar and different aspects of Uzbek and German weddings from a linguistic and cultural point of view is analyzed from the point of view. point of view.